1989
DOI: 10.1093/jnci/81.23.1794
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Laminin Receptor Antibody Targeting of Liposomes With Encapsulated Doxorubicin to Human Breast Cancer Cells In Vitro

Abstract: The tumor cell laminin receptor is a cell-surface protein that binds laminin with high affinity (Kd = 1.0 nM). The putative ligand-binding domain of the laminin receptor has been molecularly cloned and sequenced. In the present study, we used the predicted amino acid sequence of the laminin receptor to generate synthetic peptide antigens and produced immunoglobulin M (IgM) anti-laminin receptor monoclonal antibodies. The disulfide bond group of the IgM molecule was used to couple the antibodies to the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Immunofluorescence studies with antipeptide G antibodies confirmed that peptide G was expressed on the cancer cell surface (CASTRONOVO et al 1991 b). In addition, a monoclonal antibody to a 37LRP-derived sequence overlapping the peptide G region competed with laminin for binding to living human metastatic breast cancer cells in vitro (RAHMAN et al 1989). These data confirmed the hypothesis that the 37LRP contained a membrane-associated domain and a cellsurface laminin-binding region, characteristics that one would expect of the 67LR.…”
Section: Membrane-associatedand Laminin-binding Domains In the 37lrpsupporting
confidence: 70%
“…Immunofluorescence studies with antipeptide G antibodies confirmed that peptide G was expressed on the cancer cell surface (CASTRONOVO et al 1991 b). In addition, a monoclonal antibody to a 37LRP-derived sequence overlapping the peptide G region competed with laminin for binding to living human metastatic breast cancer cells in vitro (RAHMAN et al 1989). These data confirmed the hypothesis that the 37LRP contained a membrane-associated domain and a cellsurface laminin-binding region, characteristics that one would expect of the 67LR.…”
Section: Membrane-associatedand Laminin-binding Domains In the 37lrpsupporting
confidence: 70%
“…Human a-thrombin, polyclonal antibodies to glycocalicin (Harmon & Jamieson, 1986) and GPIV (Tandon et al, 1989a) and polyclonal antibody to the laminin receptor of pooled human breast carcinoma tissue (Wewer et al, 1986) had been previously produced in our laboratories. Monoclonal IgM antibodies 3D1 and 6G4 to synthetic peptide (Leu-33-.His) of the 67 kDa laminin receptor had been prepared as described (Rahman et al, 1989). Fab fragments were prepared using immobilized papain and Protein A according to the protocol of the manufacturer (Pierce Chemical Co., Rockford, IL, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…Wewer et al first indicated that anti-67LR/37LBP antisera raised against a 20-mer peptide partial sequence blocked the surface interaction of melanoma cells with endogenous laminin, resulting in the inhibition of laminin-mediated cell attachment and migration. 12) Rahman et al 27) have reported that anti-67LR/ 37LBP antibody-coupled liposomes encapsulating an anticancer drug selectively killed breast cancer cells. Iwamoto et al 28) demonstrated that synthetic YIGSR peptide, derived from the sequence of the laminin B1 chain and reported to be a binding site for 67LR/37LBP, 29) inhibited experimental metastasis of B16 melanoma.…”
Section: Discussionmentioning
confidence: 99%